Pengaruh Pemanfaatan Platform Ruang Guru dan Tenaga Kependidikan (GTK) dan Motivasi Guru terhadap Kompetensi Pedagogik Guru Sekolah Dasar di Kecamatan Turikale Kabupaten Maros: Penelitian Kuantitatif - Amin, Asriani; Sahabuddin, Erma Suryani; Makkasau, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the overview of the utilization of the Teacher and Education Personnel Space Platform (GTK) and teacher motivation in elementary schools in the Turikale district, Maros regency. It also seeks to determine the description of the pedagogical competence of elementary school teachers in Turikale district, Maros regency. Additionally, it aims to assess whether there is an influence of the utilization of the Teacher and Education Personnel Platform (GTK) and teacher motivation on the pedagogical competence of elementary school teachers in Turikale district, Maros regency. The results of this study indicate that 1) The utilization of the Teacher and Education Personnel Platform (GTK) and teacher motivation is consistently aligned with all indicators of its utilization within the favorable category group. 2) The pedagogical competence of elementary school teachers in Turikale district, Maros regency consistently falls within the dominant high category. 3) Based on data analysis, it is found that the value of The influence of the utilization of the Ruang Guru Platform and Educators (GTK) and teacher motivation on the Pedagogical Competence of Elementary School Teachers in the Turikale District of Maros Regency is indicated by a value of 6.317 with a significance level of 0.004, showing that there is a significant influence among the three variables in this study. This difference is also supported by the results of the hypothesis test, where the significance value of 0.004 < 0.05 indicates that H0 is rejected and H1 is accepted. There is an influence of the utilization of the Ruang Guru Platform and Educators (GTK) and teacher motivation on the Pedagogical Competence of Elementary School Teachers in the Turikale District of Maros Regency.